Supercritical CO2-assisted regulation of FeOOH hydrophilicity for FeIV=O deployment in aqueous waste disintegration - Kim, Minsung; Kim, Sang Hoon; Kim, Jongsik (Pergamon Press Ltd., 2025)
FeOCl and FeOOH are iso-structural and impart defective [Fe3+(O2-)4(Cl-)2]7-and [Fe3+(O2-)4(OH-)2]7-subunits on their surfaces, respectively, where Fe delta+ and Fe3+ defects can evolve center dot OH/FeIV=O and center dot OOH/O2 center dot-/1O2 in H2O2-containing aqueous media, respectively. FeOCl surface can incur marked Fe delta+/3+ leaching or rigid coordination to aqueous organics, thereby limiting its use as a reactive oxygen species (ROS) evolver and/or reservoir in aqueous phases. Conversely, FeOOH surface can avoid Fe delta+/3+ leaching by eliminating OH-ligands or their protonated analogs (H2O/H3O+) from Fe delta+/3+ in defective [Fe3+(O2-)4(OH-)2]7-sub-units. This was enabled by extensive exposure of FeOOH to supercritical CO2, producing hydrophobic FeOOH-CO2 that offered bunched merits over hydrophilic FeOOH. The number of Fe delta+ defects and their electron affinity were greater and lower, respectively, in FeOOH-CO2 than in FeOOH, resulting in higher center dot OH productivity for the former and higher 1O2 productivity for the latter, alongside with FeIV=O evolution for FeOOH-CO2. Moreover, FeOOH and FeOOH-CO2 exploited center dot OH/1O2 and FeIV=O as their primary ROS for disintegrating aqueous organics, respectively, whose inclusion of e--donating groups made FeIV=O particularly effective in initiating or propagating the destabilization of hard-to-dissociate organics via electron transfer. Furthermore, despite minimized Fe delta +/3+ leaching across FeOOH/FeOOH-CO2 surfaces, FeOOH-CO2 outcompeted FeOOH in providing higher H2O2/center dot OOH/O2 center dot- accessibility to Fe delta+/3+ defects and in avoiding their coordination to fragmented organics in H2O2-and organic-containing aqueous media. Consequently, FeOOH-CO2 was more active in, selective to, and reusable for degrading e--donating group-bearing contaminant or mineralizing textile wastewater than FeOOH, Fe2O3/Fe3O4, and FeOCl.